The gods must be crazy [videorecording (DVD)] - N!xau; Weyers, Marius; Prinsloo, Sandra; Uys, Jamie; Uys, Jamie; Uys, Jamie (Columbia TriStar Home Entertainment, 2004)
An empty Coke bottle drops from the sky near Xixo, an African San hunter, but after it causes trouble to the group, he tries to return the bottle to the gods who must have dropped it.